Social Inequality and Social Stratification in US Society - Doob, Christopher Bates (Pearson, 2013)
Keywords: Equality; United States; United States; Social stratification; dept.soc; faculty_collection

Twenty-first-century trends in highly skilled migration - Eich-Krohm, A. (Routledge International Handbook of Migration Studies, 2013)
Keywords: dept.soc

Connecticut - Kenty-Drane, Jessica L.; Prince-Stewart, Jamilah (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Keywords: dept.soc

Wealth and education - Kenty-Drane, Jessica L. (Sociology of Education: An A-to-Z Guide, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field draws contributions from education, sociology, human development, family studies, economics, politics and public policy. Sociology of Education: An A-to-Z Guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored. Despite an abundance of textbooks and specialized monographs, there are few up-to-date reference works in this area. Features & Benefits: 335 signed entries fill 2 volumes in print and electronic formats, providing the most comprehensive reference resource available on this topic. Cross-References and Suggestions for Further Reading guide readers to additional resources. A thematic "Reader's Guide" groups related articles by broad topic areas as one handy search feature on the e-Reference platform, which also includes a comprehensive index of search terms, facilitating ease of use by both on-campus students and distance learners. A Chronology provides students with historical perspective on the sociology of education.
Keywords: dept.soc